Clinical Aspects Of Measles Virus Implications In Gingival Pathology - Ioana Rudnic; Erica Rudnic; Popa Vanda; Danila Catalina; Maria Ursache; Silvia Martu (Romanian Society of Oral Rehabilitation, 2009)
Introduction: Although the role of viruses in the pathology of gingival and periodontal lesions was recently found (Contreras, 2000), periodontal literature, typically, does not include measles virus infection in the differential diagnosis of adult gingivitis and periocoronaritis associated with systemic diseases. The mechanism by which measles virus induces inflammation around coronary part of the tooth is still unclear. As herpetic viruses, may reduce periodontal defence by initiating or promoting cytotoxic events pathogenic which promote the growth of subgingivale bacteria capable of producing gum lesions (Contreras, 1999). Aim: Because of the infectious potential of this eruptive diseases ( chicken pox is an infectiousness potential of 80-85% from exposed contacts ), the dentist has to identify any of these cases from the patients requiring for dental assistance. This clinico-statistical study aimed at the total assessment of oral manifestations caused by measles virus infection in line with the general clinical picture, results of laboratory examinations, and general demographic characteristics. Material and method: We selected a group for the study consisting of 32 persons with the diagnosis of measles from the Clinical Hospital of Infectious Diseases of Iasi, between January 2005 and December 2007. From the total number of 32 patients of the study group, 16 were male and 16 sex female. Results and Discussion: Most cases of measles (59.4%) did not show obvious signs of clinical damage of oral mucous membrane (this is explained by the probability of the hospitalization for a large number of days from onset of the disease). From the clinical examination of the patients, we noticed the presence of intraoral manifestations in 8 cases (25.0%) which had very eritematous gingival mucous membrane (even in the absence of specific factors for gingival pathology as local irritation - called " gingival measles " ).